Hubungan Pengetahuan Masyarakat Pemelihara Anjing Tentang Bahaya Rabies Terhadap Partisipasi Pencegahan - Herlinae Herlinae; Yemima Yemima; Jowan Roda'i (Fakultas Peternakan Universitas Kristen Palangka Raya, 2013)
Rabies or hydrophobia which can be transmitted from animals to humans through the bite incident. Prevention and control of infectious Rabies diseases in animals and humans needs to be done. Cases of dog bites in humans often occurs in Central Kalimantan is no exception in Kabupaten Barito Selatan, and more specifically on Kecamatan Dusun Selatan. This descriptive study using a questionnaire which was distributed to 50 respondents in Kelurahan Hilir Sper. Data analysis with multiple linear regression statistical tests to see the impact of knowledge on prevention participation. Results obtained both categories of knowledge and participation of both categories. Analysis of the results of that knowledge does not affect the level of participation of rabies prevention.